2016
DOI: 10.1021/jacs.6b05848
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Titrations for Measuring the Capacitance of Colloidal Photodoped ZnO Nanocrystals

Abstract: Colloidal semiconductor nanocrystals offer a unique opportunity to bridge molecular and bulk semiconductor redox phenomena. Here, potentiometric titration is demonstrated as a method for quantifying the Fermi levels and charging potentials of free-standing colloidal n-type ZnO nanocrystals possessing between 0 and 20 conduction-band electrons per nanocrystal, corresponding to carrier densities between 0 and 1.2 × 10(20) cm(-3). Potentiometric titration of colloidal semiconductor nanocrystals has not been descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 50 publications
5
63
0
Order By: Relevance
“…In previous studies on Cu 2 S 13 and CdSe 9c our group has showed a strong effect of the size of the charge compensating ions on the reduction of nanocrystals. Furthermore, it has been shown by Brozek et al 25 that the charge compensating cation can affect both the injected electron stability and the chemical reduction of ZnO nanocrystals greatly. Therefore, a ZnO QD film was subsequently immersed in four different electrolyte solutions, containing different cations: lithium (Li + ), tetramethylammonium (TMA + ), tetrabutylammonium (TBA + ), and tetraoctylammonium (TOA + ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In previous studies on Cu 2 S 13 and CdSe 9c our group has showed a strong effect of the size of the charge compensating ions on the reduction of nanocrystals. Furthermore, it has been shown by Brozek et al 25 that the charge compensating cation can affect both the injected electron stability and the chemical reduction of ZnO nanocrystals greatly. Therefore, a ZnO QD film was subsequently immersed in four different electrolyte solutions, containing different cations: lithium (Li + ), tetramethylammonium (TMA + ), tetrabutylammonium (TBA + ), and tetraoctylammonium (TOA + ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…The identity of the charge-compensating counteraction induces systematic shifts in the Fermi level ( E F ), having important implications on the electronic properties of the NC. 39 For example, in the case of ZnO nanocrystals, the charge storage equilibrium is mainly determined by the ethanol (EtOH) oxidation process, where two EtOH molecules accept extra holes from the NC, resulting in the formation of acetaldehyde (ZnO + ½CH 3 CH 2 OH → ZnO − + H + + ½CH 3 CHO). 14 The maximum storage in ZnO NCs is thermodynamically defined by the reverse process, in which acetaldehyde is hydrogenated, hindering the accumulation of additional electrons (ZnO − + H + + ½CH 3 CHO → ZnO + ½CH 3 CH 2 OH).…”
Section: Photodoping and Multi-charge Accumulation Of Doped Mo Ncsmentioning
confidence: 99%
“…The bilayer roughly acts as a dielectric layer in a conventional capacitor. 47–49 The charge separation is around a few angstrom 50 and implemented in the following equation for the double-layer capacitance ( C dl ): 39 with A , ε 0 , ε r , and r referring to the sphere's surface area, the permittivity of free space, the dielectric constant of the solvent, and the nanocrystal radius, respectively. This equation is the extension of the classical electrostatic capacitor ( , with d being the separation of the plates) by an additional term that accounts for the thickness t of the electrical double layer.…”
Section: Determining the Capacitance Of Photodoped Mo Ncsmentioning
confidence: 99%
See 1 more Smart Citation
“…polyoxovanadate anions,51 and semiconductor nanocrystals 61,62,[67][68][69][70]. In these systems, Lewis acidic ions, e.g., Na + , Ca 2+ , Sc 3+ , modulate redox potentials by hundreds of mV through electrostatic interactions.…”
mentioning
confidence: 99%